Price promotions and brand equity: the role of brand types - Tobias Kuntner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Purpose - This study investigates whether the influence of selected marketing-mix elements on brand equity differs for different types of brands. The main focus is on price promotions' influence. In addition, the impact of discount-store distribution is explored. Design/methodology/approach - This study applies fixed-effects regression to analyze German panel data, which includes 126 national brands in four product categories across five years. Findings - The results reveal that frequent price promotions and intensive discount-store distribution have a negative influence on brand equity. However, this effect differs across brand types: the higher a brand's initial equity level, the more harmful is the impact of these marketing activities on brand equity. Research implications - This study shows that brand types play an important role in moderating the influence of marketing activities on brand equity. Thus, further research endeavors may generate new insights by accounting for these brand-related differences in their investigations. Practical implications - Managers of high-equity brands should avoid frequent price promotions and intensive discount-store distribution. In contrast, managers of low-equity brands may use these instruments more widely because their detrimental effects are less severe. Originality/value - Current research mainly focuses on improving the conceptualization of brand equity or exploring different kinds of marketing-mix elements. Findings on potential effect moderators are scarce. Thus, this study substantiates and extends existing findings by emphasizing the importance of distinguishing different brand types when investigating the effect of marketing-mix elements on brand equity.
Additional information: Part of doctoral dissertation, University of Hamburg, Submitted 10.03.2016, Examiners: Prof. Dr. Thorsten Teichert, Prof. Dr. Karen Gedenk
Keywords: 330; Price promotion; Brand equity; Brand type; Panel data